: Response of Growth and Production of Romaine Lettuce Plants to Automated Aeration of Floating Raft Hydroponic Systems - Desti Srinadila; Ummu Kalsum; Edi Minaji Pribadi (Jurnal Agroekoteknologi dan Agribisnis, 2024)
Romaine lettuce is a nutritious leaf vegetable with a high selling price and its production can be increased using a hydroponic system. Floating raft hydroponics is a hydroponic system with plants floating on styrofoam and their roots submerged in a nutrient solution. Providing aeration using an aerator connected to a timer switch is necessary to increase dissolved oxygen in the nutrient solution to optimize plant growth and production. This research aims to analyze the effect of aeration automation and the best aeration duration on the growth and production of romaine lettuce plants in a floating raft hydroponic system. The research was conducted at Greenhouse UG Technopark in May-June 2023. This experiment used a one-factor Completely Randomized Design with 4 aeration duration treatments: no aeration (control), 6 hours aeration/day, 15 hours/day aeration, and 24 hours/day aeration. Each treatment was repeated 5 times so that there were 20 experimental units and consisted of 5 samples for a total of 100 samples. The results of this research show that aeration 24 hours/day has a real influence on the parameters of plant height in the 3rd week, leaf length, leaf width, leaf wet weight, and root shoot ratio (P<0,05). Aeration 24 hours/day provides the best results for the growth and production of romaine lettuce plants. Aeration automation of 15 hours/day can be used as an alternative from the producer's side to reduce electricity use.